Edible species offered for sale in the Emiliano Zapata market in Puebla, Mexico - Reyes-Matamoros, Jenaro; Martínez-Moreno, David; Basurto-Peña, Francisco; Ibarra-Reyes, Atziri Alicia (Acta Universitaria, 2019)
Markets are places of interest where collected and domesticated plants that people use for their benefit are on sale. Therefore, the aim of this study was to register the edible species that are commercialized in the Emiliano Zapata market in Puebla, Mexico. Open interviews were held with traders to establish the places that offer fruits and vegetables, their usage and origin. The results show that 42% of places sell fruits, 35% vegetables, and 23% both. The number of botanic families was 39, with 65 genera and 100 species; the families with the highest number of species were Rutaceae and Solanaceae. In fruits, 22 species of fruits and 44 species of vegetables with a greater presence were identified. The most traded organs are the fruit, leaf, stem, root, and seed.